Electropolymerization of PPy, PEDOT, and PANi on WO3 nanostructures for high-performance anodes in Li-ion batteries - Gemma Roselló-Márquez; Dionisio Miguel García-García; Mireia Cifre-Herrando; José García-Antón (Heliyon)
In this research work, four distinct WO3 electrodes were synthesized and coated with three different polymers, known as polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) in poly(4-styrenesulfonate) (PEDOT:PSS) and polyaniline (PANi), using electropolymerization techniques. The morphological features of the samples were thoroughly characterized through Field Emission Scanning Electron Microscopy (FE-SEM) and Atomic Force Microscopy (AFM) analyses. Additionally, contact angle measurements and electrochemical characterizations were used to verify the performance of each electrode, aiding in the prediction of their suitability for energy storage applications in lithium-ion batteries. The electrodes were subsequently employed as anodes in lithium-ion batteries, and charge-discharge cycles were performed to analyze its specific capacity, and the Electrochemical Impedance Spectroscopy (EIS) technique was employed to analyze its behavior both before and after cycling. The results revealed superior performance for WO3 electrodes with PEDOT:PSS coating electropolymerized during 100 min at 0.4 mA. This comprehensive investigation not only sheds light on the synthesis and morphological characteristics of WO3 electrodes but also highlights the crucial role of PEDOT:PSS in enhancing electrochemical behavior for efficient energy storage applications.